The role of ferroptosis in neurodegenerative diseases - Fei, Yifan; Ding, Yifei (Frontiers in Cellular Neuroscience, 2024)
Ferroptosis represents an iron -and lipid peroxidation (LPO)-mediated form of regulated cell death (RCD). Recent evidence strongly suggests the involvement of ferroptosis in various neurodegenerative diseases (NDs), particularly Alzheimer's disease (AD), Parkinson's disease (PD), Huntington's disease (HD), multiple sclerosis (MS), and amyotrophic lateral sclerosis (ALS), among others. The treatment of ferroptosis poses both opportunities and challenges in the context of ND. This review provides a comprehensive overview of characteristic features, induction and inhibition of ferroptosis, highlighting the ferroptosis inhibitor and the underlying mechanisms responsible for its occurrence. Moreover, the review explores how these mechanisms contribute to the pathogenesis and progression of major neurodegenerative disorders.Additionally, it presents novel insights into the role of ferroptosis in ND and summarizes recent advancements in the development of therapeutic approaches targeting ferroptosis. These insights and advancements hold potential to guide future strategies aimed at effectively managing these debilitating medical conditions.